2023
DOI: 10.1186/s12915-023-01572-8
|View full text |Cite
|
Sign up to set email alerts
|

Guanine crystal formation by bacteria

Abstract: Background Guanine crystals are organic biogenic crystals found in many organisms. Due to their exceptionally high refractive index, they contribute to structural color and are responsible for the reflective effect in the skin and visual organs in animals such as fish, reptiles, and spiders. Occurrence of these crystals in animals has been known for many years, and they have also been observed in eukaryotic microorganisms, but not in prokaryotes. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Our findings are in line with similar recent results for seven biogenic guanine crystalline samples, where intracrystalline dopants, such as hypoxanthine and xanthine, were observed . More generally, in biogenic systems, it was shown that the guanine crystals are not pure, but occlude homogeneous mixtures of other purines, even in large amounts (up to 20% of hypoxanthine), without significantly altering the crystal structure of the guanine host. , However, unlike synthetic doped guanine crystals studied by other authors, the dopants were not thought to exert a significant influence over crystal shape or optical properties.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with similar recent results for seven biogenic guanine crystalline samples, where intracrystalline dopants, such as hypoxanthine and xanthine, were observed . More generally, in biogenic systems, it was shown that the guanine crystals are not pure, but occlude homogeneous mixtures of other purines, even in large amounts (up to 20% of hypoxanthine), without significantly altering the crystal structure of the guanine host. , However, unlike synthetic doped guanine crystals studied by other authors, the dopants were not thought to exert a significant influence over crystal shape or optical properties.…”
Section: Resultssupporting
confidence: 93%
“…24 Very recently, prokaryotes were found for the first time to produce guanine monohydrate crystals. 25 To date, there are a total of three different guanine crystal forms reported, the α 26 and β 18 anhydrous polymorphs and one monohydrate. 27 Interestingly, even though both anhydrous phases exhibit similar crystal morphology, in all cases where the crystalline form of the biogenic guanine was determined (spiders, fish, and copepods), the β polymorph was identified, 18 while the α form was obtained only in vitro.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, the inability to directly determine the structures of biogenic crystals has limited the rate of progress in organic biomineralization. We anticipate that 3D ED will play a major role in the future exploration of recently discovered uncharacterized molecular biocrystals. ,, …”
Section: Discussionmentioning
confidence: 99%
“…16,52,53 CCDC 2304787 contains the supplementary crystallographic data for the spider guanine structure reported in this paper. These data can be obtained free of charge via www.ccdc.cam.ac.uk/data_request/cif, or by emailing data_request@ccdc.…”
mentioning
confidence: 99%